PERANCANGAN BILAH INVERSE TAPER BERBAHAN STYROFOAM DENGAN AIRFOIL NACA 4412 - Simon Petrus Sidabutar; Kardiman Kardiman; Rosmawan Arwinda Setyaningrum (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2021)
In the manufacture of wind turbines, there are several parameters that are taken into account, namely the wind speed in the area to be installed. The wind speed in Indonesia ranges from 3m/s – 11m/s, so it is quite difficult to implement a macro-scale wind turbine and the facilities are still inadequate. So this design is a design to make a micro-scale wind turbine that adapts to the characteristics of wind speed in Indonesia. In this design, a blade with the Inverse Tapper type is made which is a blade type with an enlarged shape to the end to get a large sweep at the end of the blade and produce a lift force that is greater than the drag force on the blade so that it can rotate the blade. In the design of this blade, material changes are also made, generally the material used in the blade is made of wood, fiber, and aluminum. In this design, a material made of styrofoam is used, this is to make the mass of the blade lighter and make the blade able to rotate at the smallest wind speed. In this design, the maximum power obtained is 553 watts at 668 rounds of blade rotations . Keywords : Airfoil, Inverse Blade, Cl/Cd, Styrofoam.